Concerns About Mesenchymal Stem Cell Therapy: Mesenchymal stem cells therapy concerns - Haseli, Mahsa; Esmaeili, Akbar (International Clinical Neuroscience Journal, 2020)
Dear Editor, Multipotent mesenchymal stromal cells (MSCs), because of their potential for treating diseases, have gained considerable attention over the past 30 years for their immunosuppressive properties and tissue regeneration capabilities.1,2 This grew into an interest in the 1970s by Friedenstein and contemporaries after studying the bone m ar row.3 MSCs are an excellent candidate for cell therapy because of having intrinsic differentiation potentials into bone, cartilage and fat cells not found previously in other cells. They can also be isolated and expanded easily in vitro, and produce abundant useful growth factors and cytokines.2,4Mesenchymal stem cells have become the top used stem cell type for clinical application with encouraging results.5,6 Significant progress has been made in stem cell research in recent years. The main therapeutic effects of MSCs are now attributed to the stimulation of several innate repair processes in injured tissues in vivo by secreted factors as well as the immunomodulation response. Therefore, MSC therapy is expected to find clinical application in human diseases.6,7 However, there are some critical issues that need to be addressed before MSCs can be used for clinical therapy in humans which will help determine the efficiency of cells administered to the patients as a therapeutic approach, most important of which is immunosuppressive properties.8,9 MSCs can be affected by tumor support that may affect potential tumorigenesis after MSCs transplantation, including different donors and tissues, inconsistent protocols, varying dosages and differing transfusion patterns, and mechanisms that control the behavior of the MSCs at the target site.10,11 Because of their unique features, stem cells are undoubtedly a great hope for the treatment of many diseases. More research is developing on the potential long-term risks associated with MSC therapy. However, Additional studies would also be a major contribution to stem cell biology in general as well as their transplantation.